Positive and negative risk in adventure tourism discourse: adrenaline hunting in “arctic Lapland” - Ädel, Annelie; Östman, Jan-Ola (Text & Talk, 2025)
Abstract ‘Risk’ is typically thought of as something negative, and as something that should be avoided at all cost: risk characteristically has to do with the probability of an unwanted event occurring. However, risk may also be seen as something positive, even energizing, as in the context of financial markets or gambling. Voluntary risk taking has typically been approached through the concepts ‘action’ and ‘edgework’. In this study, both negative and positive aspects of risk are explored in the context of adventure tourism. The focus is on how risk is discursively constructed in adventure tourism websites for Sápmi, centring on destinations in Sweden (Kiruna), Finland (Rovaniemi) and Norway (Tromsø). Our primary material from the booking platform Adrenaline Hunter amounts to 12,000 words. The findings show an ambivalence between negative and positive aspects of risk, but in a scalar sense, ranging from “soft” to “hard” types, with a negotiable awareness of how relative what counts as “extreme” may be. The theoretical suggestion is that positive aspects of risk need to be taken seriously for a fuller understanding of the very concept of ‘risk’ and of the workings of risk discourse.